Parallels between Yakubinsky and Bakhtin: distancies - Santos, Robson (2010)
This study proposes a discussion about the work of Yakubinsky and his early influence on the Bakhtin Circle, by analyzing the distances theoretical between Yakubinsky and Bakhtin who settled later. From the original article Yakubinsky Dialogic Speech, was identied some aspects that show conceptual distances with the later work developed by Bakhtin, constituting a parallel between the two authors, especially the automation of discourse, or the character psychophysiological defended by Yakubinsky and a dialogism of philosophical wider built by Bakhtin.